Is Gastroparesis Found More Frequently in Patients with Cystic Fibrosis? A Systematic Review - Juan E. Corral; Corey W. Dye; Maria R. Mascarenhas; Jamie S. Barkin; Matthias Salathe; Baharak Moshiree (Scientifica)
Cystic fibrosis (CF) is associated with different gastrointestinal motility disturbances and syndromes. We aim to assess gastric emptying in patients with CF compared to healthy controls by a systematic review of existing literature. Medical databases and abstracts from major gastroenterology and CF meetings were reviewed. Emptying times in CF patients were compared with healthy controls using random effects models. Subgroup analysis stratified results by age and diagnostic modality. Nineteen studies from 7 countries included 574 subjects (359 CF patients and 215 controls). Using pooled analysis frequency of gastroparesis was high (38%, 95% CI 30–45%) but results were highly dependent on the diagnostic modality. Delayed gastric emptying is more common in CF compared to general population. Scintigraphy identified rapid gastric emptying in a subgroup of CF patients, but this finding disappeared with adequate pancreatic enzyme replacement and after other diagnostic modalities were included.